Development and validation of stability indicating RP-HPLC method for Simultaneous determination of Desloratadine and Montelukast Sodium in pharmaceutical dosage form - Ravi Challa; N.V.S. Naidu (International Journal of Pharmacy and Analytical Research, 2016)
A simple, precise cost effective and stability indicating RP -HPLC method has been developed and validated for simultaneous determination of Desloratadine (DES) and Montelukast sodium (MKT) in pharmaceutical formulation. The RP-HPLC was performed on Zodiac C18, (100mmx4.6mm, 5µ particle size) column. Mobile phase consisting of mixed buffer and methanol in the ratio 40:60 v/v. (2.6 gms of potassium hydrogen phosphate and 0.6 gms of dipotasssium hydrogen phosphate in 1000 ml distilled water, pH was adjusted to 6.0±0.1 with dilute orthophosphoric acid) and column temperature was 30oC. The flow rate of the mobile phase was 1.0 ml/min and the injection volume was 20μl. Detection was performed at 261nm.The Retention time for DES and MKT were 2.460 and 3.129 min respectively. The method was validated and shown to be linear for DES and MKT in 2.5-15.0 μgmL-1 and 5.0-30.0 μgmL-1 respectively. The regression was 0.9997 for DES and 0.999 9 for MKT. DES and MKT were highly susceptible to acid (33.18 & 35.49), peroxide conditions (35 & 32.39) and least susceptible to UV (2.22 & 2.52) and basic conditions (2.59 & 3.73). Precision studies showed % RSD values less than 2% for both the drugs in all the selected concentrations. The percentage recoveries of MKT and DES were in the range of 99.40%-99.99%and 99.18%-100.45% respectively. The limit of detection (LOD) and limit of quantification (LOQ) were 0.084μg/ml, 0.254μg/ml for MKT and 0.081 μg/ml, 0.246μg/ml for DES respectively. The method was validated as per the International Conference on Harmonization (ICH) guidelines.